The Biblical Hermeneutics of Noetus of Smyrna - Morales, Xavier (Zeitschrift für antikes Christentum, 2023)
Noetus of Smyrna, who probably lived at the end of the 2d century, was proclaimed the father of modalism by the history of dogmas. His character, eclipsed by his successors to the role of the main representative of modalism (Sabellius or Marcellus of Ancyra), remains enigmatic. The two main documentary sources, Against Noetus ( Contra Noetum ) and Refutation of All Heresies ( Refutatio omnium haeresium ), give a discordant presentation of him: defender of a naïve interpretation of biblical monotheism or inventor of a Christian heracliteism? This article, after a brief historical introduction, studies the scriptural hermeneutics of the Smyrniot to show that Noetus is not a simplistic exegete or a narrow-minded theologian. His theology of divine identity, which it is wrong to call modalism, is based on an intelligent analysis of the Scriptures.